Isolation and partial characterization of a lectin from synometra tamiflora - Bantilan, Teresita T.
A preliminary survey of lectin activity was done on the seed extracts of eighteen species of plants. Six of the plants species had lectin activity and Cynometra remiflora was chosen as source of lectin because it exhibited the highest activity. The lectin was isolated from the seeds of Cynometra ramiflora by extraction with normal saline solution (NSS) and purified by high-pressure gel permeation chromatography using the Protein Analysis Column I-125. Ammonium sulfate fractionation and gel filtration on Sephadex G-100 failed as purification methods for the lectin extract. The lectin isolate was found to be non-specific. It agglutinated human erythrocytes of blood groups A, O and B including the erythrocytes from crow, carabao, goat and swine. It failed to agglutinate rabbit erythrocytes. SDS-gel electrophoresis showed that the lectin has a molecular weight of about 14, 400-16,200. It is highly acidic protein with isoelectric pH below 3.5.
Theses--(MS in Biochemistry) University of the Philippines Manila
Keywords: Lectins; Cynometra Ramiflora